Antimicrobial and antibiofilm forming activity of Origanum munzurense against some Gram-Positive bacteria and yeast - Zeybek, E; Kart, A; Yalcin, H (Journal of the Hellenic Veterinary Medical Society, 2023)
In vitro antimicrobial and antibiofilm forming activities of Origanum munzurense extract were investigated against some gram-positive bacteria and yeast strains. Liquid microdilution method and microplate method were used for antimicrobial and antibiofilm forming activities, respectively. Minimal inhibitory concentration values were found to be 2 mg/ml for Enterococcus faecalis ATCC 29212, 64 mg/ml for Listeria monocytogenes RSKK 02028, 2 mg/ml for L. monocytogenes RSKK 472, 2 mg/ml for Bacillus cereus NRRL 569 , 128 mg/ml for S. aureus ATCC 25923, 32 mg/ml for S. aureus (MRSA) ATCC 43300 strain, 64 mg/ml for Candida tropicalis ATCC 13803, 2 mg/ml for C. albicans ATCC 90028, 1 mg/ml for S. aureus FRI 918 and 1 mg/ml for Staphylococcus epidermidis ATCC 12228 strain. The extract prevented the biofilm formations of E. faecalis ATCC 29212, S. aureus FRI 918 and S.epidermidis ATCC 12228 at concentrations of 2 mg/ml, 500 µg/ml and 250 µg/ml, respectively. No biofilm formation was observed for the other bacteria tested.As a result, Origanum munzurense extract has antibacterial and antibiofilm activity on the selected pathogenic microorganisms tested. Due to these properties of O. munzurense, it could be considered as a plant-based antimicrobial agent to be used especially in the food industry.